THE INFLUENCE OF MARKETING MIX ON PURCHASING DECISIONS OF HERBAL MEDICINE CONSUMERS AT CV AA - wisanggeni, helmi; hermeindito (Universitas Nahdlatul Ulama Surabaya, 2024)
The increasing demand for herbal medicine, particularly in the form of jamu, in Indonesia presents a business opportunity for jamu producers. The growing number of jamu producers has led to intense competition, prompting companies to meet consumer needs, expand their market reach, and innovate to maintain and dominate the market with their products. This research aims to determine the influence of the 4Ps marketing mix on consumer purchase decisions for CV AA's jamu products. This study adopts a quantitative approach. The population consists of consumers who purchase CV AA's jamu products throughout Indonesia. Based on the Slovin formula, the sample size for this study is determined to be 141 individuals. Data collection is done through an online questionnaire using Google Forms, and the analysis technique used is multiple linear regression. The results of this study show that product, price, promotion, and place have a positive and significant influence on consumer purchase decisions for CV AA's jamu products. To improve consumer decisions, CV AA should continually enhance the quality of its jamu products, set competitive prices that align with the value offered, utilize effective promotional channels, and improve distribution efficiency while ensuring product availability in various sales locations.